PENYEDIAAN TAMAN BACA SEBAGAI SOLUSI MINAT BACA DI DESA SINARMUKTI - Fikri Yansyah; Anton Nasrullah; Handy Sahrio; Eti Kuryati; Rani Puspa; Puput Sumiati; Siti Ridha Nurfadilah; Iim Soimin (Yayasan Education and Social Center, 2021)
With the Community Reading Park activity, this program tries to improve literacy in villages during the pandemic. The Sinarmukti village community is the focus of community service. Community service, one of the government programs that refer to the laws of the Unitary State of the Republic of Indonesia, is to organize educational programs in the Community Reading Park (TBM) program. A reading garden aims to create a space where people can expand their knowledge, understanding and expertise and better understand the world around them. The purpose of this activity is to reach people who like to learn. Furthermore, TBM activities promote literacy and expand access by offering opportunities for the community to obtain educational services